Antropologiczny kontekst w teologii sakramentu pokuty i pojednania - Kucza, Grzegorz (Studia Pastoralne, 2007)
In our dissertation attention is concentrated on the sacrament of penance and reconciliation. The fundamental aim is to consider the anthropological dimension of this sacrament. The sacrament of penance, like all the sacraments, is a personal meeting between God and an individual person. Its intent and purpose is to restore that individual's relationship to God: that is, the community of life with Him, lost by sin. The sacrament is not only reconciliation with God, but also with the Church and with other people. Man is reconciled with himself, and what is more, with the whole world. The sacrament of penance and reconciliation is a precious gift given man by a God of Mercy, who is the Father of Mercy and the source of all forgiveness. The sacrament is also a challenge for a person to become totally involved in the process of internal conversion. It builds the identity and integrity of a human being. It allows an individual to find himself and his vocation to live the Divine Life. Finally, it remains the only obvious way of an individual's personal development, the aim of which is to reach human holiness. Our responsibility to freedom is also constantly strengthened by this sacrament.